Pesnitve sodobnih slovenskih pesnic - Pavlič, Darja (Jezik in slovstvo, 2021)
Among the literary genres that characterise Slovenian poetry, long poems have not been prominent, and especially not long poems written by women. In recent years, however, women poets have written a number of works that fit this label, demonstrating their great creative power. In this paper, I first discuss the theory and history of the long poem, devoting particular attention to the diversity of long poems in American poetry, and then analyse recent works by Nina Dragičević, Katja Gorečan and Kristina Hočevar by exploring the poetic processes and themes employed. All of the works under consideration belong to modernist and experimental poetry, and they are all characterised by hybridisation of genres and the dissemination of literature with other media. On a thematic level, they are linked by their treatment of various forms of violence in contemporary society.
Keywords: 21. stoletje; 21st century; Dragičević, Nina; Gorečan, Katja; Hočevar, Kristina; long poem; pesnitev; Slovenian literature; Slovenian poetry; Slovenian women poets; Slovenska poezija; Slovenske pesnice